2022
DOI: 10.1002/jhm.12979
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the I‐PASS handoff program in diverse clinical environments: A multicenter prospective effectiveness implementation study

Abstract: Background: Handoff miscommunications are a leading source of medical errors.Harmful medical errors decreased in pediatric academic hospitals following implementation of the I-PASS handoff improvement program. However, implementation across specialties has not been assessed.Objective: To determine if I-PASS implementation across diverse settings would be associated with improvements in patient safety and communication. Design: Prospective Type 2 Hybrid effectiveness implementation study. Settings and Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…27–29 However, these process improvements have been at best surrogates for improved patient care, and recent reviews and a national consensus panel found no direct such evidence and encouraged an emphasis on finding it as a top priority. 30–32 Recently, implementation of the “I-PASS” structured handover tool in medical and pediatric hospitalist services (accompanied by extensive education and training of personnel) was associated with a reduction of self-reported “handoff-related adverse events.” 33 Our data suggest that in the setting of a high frequency of anesthesia handovers, use of a structured tool may reduce the risk of the change of personnel.…”
Section: Discussionmentioning
confidence: 72%
“…27–29 However, these process improvements have been at best surrogates for improved patient care, and recent reviews and a national consensus panel found no direct such evidence and encouraged an emphasis on finding it as a top priority. 30–32 Recently, implementation of the “I-PASS” structured handover tool in medical and pediatric hospitalist services (accompanied by extensive education and training of personnel) was associated with a reduction of self-reported “handoff-related adverse events.” 33 Our data suggest that in the setting of a high frequency of anesthesia handovers, use of a structured tool may reduce the risk of the change of personnel.…”
Section: Discussionmentioning
confidence: 72%
“…Recall bias was likely also limited as surveys were sent to admitting clinicians within 72 hours after IHT patient admission. Additionally, prior data suggest high correlation between clinician-reported medical error rates and those captured by other more resource-intensive methodologies (eg, targeted medical record review), 24 29 and the improvement seen in clinician-reported events was accompanied by similar improvements in more objective patient outcomes. Another potential limitation is confounding due to differences in patient populations during the two study periods, as noted in table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence-based tools for hospice handoffs do not exist [34], lessons learned from tools in other settings among patients with serious illness may be of value to adapt a structured handoff process for hospice transitions. The five quality patient handoff components from the evidence-based I-PASS handoff project include the following topics: illness severity (I), patient summary (P), action list (A), situational awareness and contingency plans (S), and synthesis by the receiver (S) [35]. A critical component of the handoff process should include a discharge checklist with components such as lists of medications and medical equipment, as well as names of clinicians and caregivers.…”
Section: Communication Approaches For Handoff Between Pulmonary/ Pall...mentioning
confidence: 99%